Altered hepatic sulfur metabolism in cystathionine β‐synthase‐deficient homocystinuria: regulatory role of taurine on competing cysteine oxidation pathways. Issue 9 (2nd June 2014) - Jiang, Hua; Stabler, Sally P.; Allen, Robert H.; Abman, Steven H.; Maclean, Kenneth N.
Abstract : Cystathionine β‐synthase‐deficient homocystinuria (HCU) is a serious life‐threatening inborn error of sulfur metabolism with poorly understood pathogenic mechanisms. We investigated the effect of HCU on hepatic cysteine oxidation in a transgenic mouse model of the disease. Cysteine dioxygenase (CDO) protein levels were 90% repressed without any change in mRNA levels. Cysteinesulfinic acid decarboxylase (CSAD) was induced at both the mRNA (8‐fold) and protein (15‐fold) levels. Cysteine supplementation normalized CDO protein levels without reversing the induction of CSAD. Regulatory changes in CDO and CSAD expression were proportional to homocysteine elevation, indicating a possible threshold effect. Hepatic and blood taurine levels in HCU animals were decreased by 21 and 35%, respectively, and normalized by cysteine supplementation. Expression of the cytoplasmic (GOT1) and mitochondrial (GOT2) isoforms of glutamic‐oxaloacetic transaminase were repressed in HCU animals by 86 and 30%, respectively. HCU induced regulatory changes in CSAD, CDO, and GOT1 expression were normalized by taurine supplementation, indicating that cysteine is not the only sulfur compound that regulates hepatic cysteine oxidation. Collectively, our results indicate that HCU induces significant alterations of sulfur metabolism with the potential to contribute to pathogenesis and that cysteine and taurine have the potential to serve as adjunctive treatments in this disease.—Jiang, H., Stabler, S. P., Allen, R. H., Abman, S. H., Maclean, K. N. Altered hepatic sulfur metabolism in cystathionine β‐synthase‐deficient homocystinuria: regulatory role of taurine on competing cysteine oxidation pathways. FASEB J. 28, 4044‐4054 (2014). www.fasebj.org